Management of Cysts of Maxillary Sinus - Alwan, Tahreer Mohsin; Alwan, Ammar Mohsin; Chichua, Nino (Caucasus Journal of Health Sciences and Public Health, 2016)
The maxillary sinuses are air-containing spaces that occupy maxillary bone bilaterally. It is the largest of the paranasal sinuses. The mucosa of the sinus is susceptible to infectious, allergic and neoplastic diseases. Inflammatory diseases of the sinus such as infection or allergic reactions cause hyperplasia and hypertrophy of the mucosa and may cause obstruction of ostium. Cyst of maxillary sinus a.k.a. Antrum of Highmore is very common complication and needs surgical treatment. Cyst is an abnormal closed epithelium-lined sac that may contain a liquid or semi-solid substance. Maxillary cysts can be of an odontogenic and non-odontogenic origin. The disease might be asymptomatic unless it has already caused irritation or pain. It can also be accidently discovered on radiographs while visiting a doctor. In some cases patient complains of sense of pressure, pain and fullness. Usually cysts are harmless, but they should be removed when possible, because the risk of becoming infected or changing into malignant growths is high. Evaluation of maxillary sinus includes clinical examination methods such as palpation, percussion, inspection of oral cavity as well as radiographic examination. Treatment of the cysts ranges from simple enucleation to curettage and to resection. The goal of sinus surgery is to remove abnormal tissue from within the sinus cavity and restore normal drainage. The cyst must be fully removed together with its shell to avoid cases of recurrence in the future. The removed cyst must be sent to histomorphologic investigation to confirm the diagnosis and to rule out other neoplastic lesions with similar clinical or radiographic features.